ANALISIS PENERAPAN PENAGIHAN PAJAK DENGAN SURAT PAKSA DALAM MENINGKATKAN PENERIMAAN PAJAK STUDI KASUS PADA KANTOR KPP PRATAMA SUKABUMI - Kirana Zahira Pujia Bangsa; Ismet Ismatullah (AJAR, 2021)
This study aims to determine the analysis of the application of tax collection by force letter in increasing tax revenue at the KPP Pratama Sukabumi office. The population and sample used were the tax authorities or tax collection officers and verifier assistants as many as 15 people at the Tax Office (KPP) Sukabumi Pratama. The sampling technique used is saturated sampling. This study uses qualitative research with an associative approach. Based on the results of research that the application of tax collection by forced letter carried out by the Tax Office of Sukabumi KPP was issued if for 21 days after the warning letter was issued and still had not been paid. Forced letters issued and sent to taxpayers as many as 896 and data on achievement of Tax Return of Pratama Sukabumi, tax revenues in 2019 amounting to Rp1,284,529,911,630.00 from the target set of Rp1,437,487,596,000.00 or equal to 89.36% of the achievement target.